Electronic Commerce 2018 A Managerial and Social Networks Perspective - Turban, Efraim (Springer Texts in Business and Economics,, 2018)
This new Edition of Electronic Commerce is a complete update of the leading graduate level/advanced undergraduate level textbook on the subject. Electronic commerce (EC) describes the manner in which transactions take place over electronic networks, mostly the Internet. It is the process of electronically buying and selling goods, services, and information. Certain EC applications, such as buying and selling stocks and airline tickets online, are reaching maturity, some even exceeding non-Internet trades. However, EC is not just about buying and selling; it also is about electronically communicating, collaborating, and discovering information. It is about e-learning, e-government, social networks, and much more. EC is having an impact on a significant portion of the world, affecting businesses, professions, trade, and of course, people. The most important developments in EC since 2014 are the continuous phenomenal growth of social networks, especially Facebook , LinkedIn and Instagram, and the trend toward conducting EC with mobile devices. Other major developments are the expansion of EC globally, especially in China where you can find the world's largest EC company. Much attention is lately being given to smart commerce and the use of AI-based analytics and big data to enhance the field. Finally, some emerging EC business models are changing industries (e.g., the shared economy models of Uber and Airbnb). The 2018 (9th) edition, brings forth the latest trends in e-commerce, including smart commerce, social commerce, social collaboration, shared economy, innovations, and mobility.